PENERAPAN METODE TOPIS PADA PENERIMAAN BANTUAN LANGSUNG TUNAI DANA DESA - Rianto, Rianto; Affindo, Edo; Wardani, Setia (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2024)
The selection of prospective recipients for Direct Cash Assistance (BLT) from Village Funds often faces the complex problem of determining the individuals who truly need assistance. This problem arises due to the limitations of the data and criteria used, as well as the lack of transparency in the selection process. This research aims to overcome these problems by applying the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method in a decision support system for selecting BLT prospective recipients. The TOPSIS method is chosen because of its ability to handle multi-attribute criteria and different weights. The data used in this research is village population data that has been surveyed and verified by the village government. The criteria used in the selection of BLT prospective recipients include poverty level, living conditions, age, Marital Status, health. The results of the study show that the TOPSIS method is able to produce a more objective and accountable ranking of BLT prospective recipients compared to conventional methods. The application of this method is expected to assist village governments in distributing assistance effectively and minimizing the potential misuse of BLT funds.